Evaluation of storage capacity of ponds and water quality analysis of tubewell and stream in a small watershed - NIGAM, G. K.; PANDEY, V. K.; TRIPATHI, M. P.; SINHA, JITENDRA (Journal of Soil and Water Conservation, 2022)
This study deals with determination of various topographic parameters, storage capacity of ponds and water quality analysis of water bodies existing in Sandhari nala watershed. Water storage capacity of 34 ponds was determined. Maximum storage capacity of the farm pond is determined on the basis of overall shape, surface area and depth of the pond. Water samples collected from the open streams and tube wells at different locations in the watershed were analyzed for their physicochemical characteristics including pH, TDS, TH, Ca++, Mg++, Na+, K+ and Cl- etc. Total storage capacity of ponds existing in the watershed was estimated to be 49, 37,000 m3. The water is used for different purposes such as domestic, irrigation, fish production etc. and farmers are being benefited in terms of crop production during both rabi and kharif seasons. Water samples of tube wells and open streams showed acidic nature. However, some other parameters available in the water samples taken from the tube well showed higher values than the open stream. As per the standard specifications the water flowing in the streams and available in the tube wells found to be suitable for domestic and irrigation purpose.